Search for WZ+ZZ production with MET + jets with b enhancement at sqrt(s) = 1.96 TeV - Collaboration, CDF; Aaltonen, T; Gonzálezv, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Apresyan, A; Arisawa, T; et al. (2011)
Diboson production ($WW+WZ+ZZ$) has been observed at the Tevatron in hadronic decay modes dominated by the $WW$ process. This paper describes the measurement of the cross section of $WZ$ and $ZZ$ events in final states with large $\mett$ and using $b$-jet identification as a tool to suppress $WW$ contributions. Due to the limited energy resolution, we cannot distinguish between partially hadronic decays of $WZ$ and $ZZ$, and we measure the sum of these processes. The number of signal events is extracted using a simultaneous fit to the invariant mass distribution of the two jets for events with two $b$-jet candidates and events without two $b$-jet candidates. We measure a cross section $σ(p\bar{p}→ WZ,ZZ) = 5.8^{+3.6}_{-3.0}$ pb, in agreement with the standard model.